2020
DOI: 10.1002/2050-7038.12670
|View full text |Cite
|
Sign up to set email alerts
|

Resiliency‐oriented islanding of distribution network in the presence of charging stations for electric vehicles

Abstract: Background: Fast Charging Stations (FCSs) for Plug-in Electric Vehicles (PEVs) can affect the performance of distribution networks due to high charging demand of a large number of PEVs. Aims: To reduce negative impacts of FCSs, the interactions between transportation and distribution networks must be taken into account in decision-making models. This paper proposes an optimization model to increase the resiliency of the distribution network after occurring severe events considering the availability of FCSs Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…One implication may be congestion of lines and transformers (this issue intensifies especially in heavily populated areas, where the electricity grid has no free capacity to meet additional loads) [194]. Other implications may be power losses [195], power quality issues [196], harmonic distortion [197], voltage drop and imbalance [198], peak load, poor load factor, thermal stress [199], frequency deviations [200], voltage instability [201], reliability deterioration [202], decreased resiliency [203], etc. The studies for the Belgium grid showed that 30 % EV penetration would result in 10 % increases in peak demand [15].…”
Section: Grid-related Challengesmentioning
confidence: 99%
“…One implication may be congestion of lines and transformers (this issue intensifies especially in heavily populated areas, where the electricity grid has no free capacity to meet additional loads) [194]. Other implications may be power losses [195], power quality issues [196], harmonic distortion [197], voltage drop and imbalance [198], peak load, poor load factor, thermal stress [199], frequency deviations [200], voltage instability [201], reliability deterioration [202], decreased resiliency [203], etc. The studies for the Belgium grid showed that 30 % EV penetration would result in 10 % increases in peak demand [15].…”
Section: Grid-related Challengesmentioning
confidence: 99%
“…With the high penetration of DGs, MG formation is an effective operational strategy to restore critical loads as major faults occur in distribution systems. Optimal methods based on heuristic search (Bajpai et al, 2016;Sedzro et al, 2018;Xu et al, 2016;Zadsar et al, 2017) and mathematical programming (Alizadeh et al, 2020;Biswas et al, 2021;Gilani et al, 2020;Momen et al, 2020Momen et al, , 2021Sedzro et al, 2017;Zhu et al, 2020) were used for MG formation problem in the resilient distribution systems. In (Bajpai et al, 2016), a methodology based on the graph-theoretic method and Choquet integral was introduced for MG formation to quantify the distribution system resilience during extreme contingencies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, environmental concerns, the security of oil supply, and the increasing penetration of intermittent renewable energy resources in the electrical network are increasing the utilization of PEVs in the transportation sector. On the other hand, the charging pattern of PEVs may affect the resiliency of the DN, which is the ability to withstand the low-probability high-impact events, ensuring the minimum load shedding (LS) and enabling a fast recovery to the normal operation state [1]. Some indicators have been presented in several articles to evaluate the power system resiliency.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal charging/discharging management of PEVs in EVPLs can offer benefits for the DN. Technically, PEVs can operate in two modes: (1) charging or grid-to-vehicle (G2V) mode as a load, and (2) discharging or vehicle-to-grid (V2G) mode as an energy storage unit [15,16]. A comprehensive review of control structures of PEVs in charging stations, objectives of EV management in power systems, and optimization methods have been presented in [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation